Research on mechanism and risk assessment of water and sand outburst in weakly cemented rock layers of Jurassic coalfields - Jiangwei FAN; Haiyu HUANG; Xiang DING; Naijun LI; Zhiguo PU; Yuguang ZHANG; Liguo ZHAO (Meikuang Anquan)
Due to the relatively late coal-forming period in the Jurassic coalfields in western China, the rock characteristics often exhibit poor cementation, low strength, and easy softening and collapse in contact with water, which leads to the occurrence of water and sand outburst events in weakly cemented rock layers during mining. Therefore, identifying the mechanism of water and sand outburst is the key to formulating corresponding prevention and control measures. Taking a certain mine in Xinjiang as the research object, by testing parameters such as rock mechanical strength and softening coefficient, it is determined that Jurassic sandstone is a typical weakly cemented soft rock formation that is prone to softening and disintegration; based on the development height of the water conducting fracture zone in the first mining face of the mine, changes in the water level of the aquifer, and analysis of the water quality of the inflow, the water source of the working face has been determined; the mechanism of water and sand outburst is determined to be the seepage of weakly cemented sandstone water along the water conducting channel formed by the fracture zone in the roof. At the same time, due to the collapse zone also connecting the direct development of the top mudstone to the sandstone layer, and the long-term cessation of mining in the working face leading to further expansion of the fractures, water eventually carries the weakly cemented sandstone that has collapsed into the mining space; by combining the water abundance of weakly cemented rock aquifers and the degree of damage to the collapse zone of the coal seam direct roof mudstone aquifer, the hazard zoning evaluation of water and sand outburst in weakly cemented rock layers was carried out.